PHYTOCHEMICAL SCREENING, ANTIMICROBIAL ACTIVITY AND BRINE SHRIMP LETHALITY BIOASSAY OF DIFFERENT EXTRACTS OF ALYSICARPUS VAGINALIS VAR. NUMMULARIFOLIUS (DC.) MIQ. (FAMILY: FABACEAE) - Kurian, Susan; Josekumar, V. S. (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Objective: To evaluate the antimicrobial activity and cytotoxicity of hexane, ethyl acetate and methanol extracts of Alysicarpus vaginalis var. nummularifolius (DC) along with phytochemical analysis. Methods: The crude extract of hexane (AVH), ethyl acetate (AVE) and methanol (AVM) of Alysicarpus vaginalis var. nummularifolius (DC) were prepared and analysed for phytochemical constituents using standard methods. The cytotoxicity activity of the plant extracts was predicted using brine shrimp lethality assay (BSLA). The antimicrobial activity and the minimal inhibitory concentration (MIC) of the plant extracts were examined against 5 bacterial and 2 fungal strains using agar well diffusion method, and two fold serial dilution method, respectively. Results: The phytochemical screening studies showed a higher concentration of saponins, alkaloids, flavonoids, phenols, quinones and terpenoids in AVM than the other two extracts. The LC50 value of AVH and AVE were found to be 900.05 µg/ml and 754.35 µg/ml respectively using BSLA while that of AVM was>1000 ug/ml. All the extracts of the plant showed antimicrobial activity against most of the test organisms. The MIC values of AVM were lower than AVE for all the microbial strains except for Pseudomonas aeroginosa where AVE (107.87µg/ml) exhibited higher value than AVM (51µg/ml). Conclusion: The present study concluded AVM with a high presence of phytochemicals. The AVE and AVM were found to possess promising antimicrobial activity when compared with the standards. The AVM exhibited lesser toxicity when compared with AVH and AVE.